1994
DOI: 10.2307/3432224
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Response to Hyperoxia: Effects of Magnesium

Abstract: Animals and humans rapidly develop respiratory failure and die within a few days when exposed to 100% oxygen. Postmortem examination of the lungs shows histopathologic features characteristic of diffuse alveolar damage, clinically recognized as adult respiratory distress syndrome (ARDS). At the present time, there is no effective therapy available to alter outcomes in ARDS. Importantly, hypomagnesemia also is frequently observed in critically ill patients at risk of developing ARDS. In a model of hyperoxic lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…There is evidence that hy~eroxiamay be related to chronic lung disease in premature infants (Kelly, 1993). Another group found that in both animals and humans, exposure to 100% oxygen causes adult respiratory distress syndrome from which death results within a few days (Dedhia and Banks, 1994). Prolonged exposure to high concentrations of oxygen is reported to cause CNS and pulmonary toxicity, resulting in atelectasis, pulmonary edema, and seizures (Jenkinson, 1993).…”
Section: Protective Nature Of Two Free Radical Scavengers 2049mentioning
confidence: 99%
“…There is evidence that hy~eroxiamay be related to chronic lung disease in premature infants (Kelly, 1993). Another group found that in both animals and humans, exposure to 100% oxygen causes adult respiratory distress syndrome from which death results within a few days (Dedhia and Banks, 1994). Prolonged exposure to high concentrations of oxygen is reported to cause CNS and pulmonary toxicity, resulting in atelectasis, pulmonary edema, and seizures (Jenkinson, 1993).…”
Section: Protective Nature Of Two Free Radical Scavengers 2049mentioning
confidence: 99%
“…Exposure to a high fraction of oxygen damages the respiratory epithelium and causes long-term fibrosis and mortality in animals and humans. In contrast, high-dose magnesium therapy has been found to alleviate the adverse effects of hyperoxia [ 52 ]. Hypomagnesemia has been found to be associated with a higher risk of mortality, sepsis, mechanical ventilation, and extended intensive care unit (ICU) stays for patients who are admitted to the ICU.…”
Section: Hypomagnesemia and Respiratory Diseasesmentioning
confidence: 99%
“…Thrombin activity requires Ca + , and parathyroid glands regulate extracellular Ca + to optimize its activity [26,[66][67][68][69][70][71][72][73][74][75][76][77][78][79]. Mg + competitively inhibits Ca + and mitigates thrombin activity [66,75,[80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96].…”
Section: The Three Srm Productsmentioning
confidence: 99%